Ultramorphometrics of Sensilla in Maxilla of Honey Bee Apis cerana Fabricius - Hutabarat, Desmina Kristiani; Nurcholis, Nurcholis; Yusuf, Mani (Central Research Institute For Agriculture, 2024)
Olfactory receptors are located in the antennae and maxillae with many sensilla found along the surface. Studies on ultramorphometric sensilla are more commonly found in the antennae. While studies on sensilla in the maxillae in bees are very few. Apis cerna as a local Asian bee has a widespread distribution in Asia and is used as a research object by utilizing the maxillae and maxillae palp. After being collected, preparations were carried out which were then identified with the help of an electron microscope. After observing the distribution, measurements were carried out using Image J. Basiconica type I and II sensilla were found in the maxillae of bees.A. cerana. The size of basiconia I sensilla is larger than type II with the most distribution found at the base of the maxilla rather than at the tip of the maxilla and maxilla palp. So that the study shows that the distribution and types of sensilla in the maxilla are more limited. This indicates the characteristics of sensilla in responding to food and their environment.